The master production schedule and uncertainty in the manufacturing sector: a systematic review of the literature - Luna-Victoria-León, Gustavo Adolfo (2022)
This research addresses two relevant topics for industrial engineering: master production plans (dependent variable) and uncertainty (independent variable). The latter constitutes a critical impact factor in the manufacturing sector. For the investigation, we collected articles related to these variables to establish the state of affairs in the specialized literature. We searched for information in two indexed databases, Scopus and ProQuest, and filtered it using inclusion and exclusion criteria derived from the PRISMA method. We identified sixteen scientific journal articles of interest for the investigation at the end of the process. These studies show essential data about the variables described and additional variables that influence uncertainty and that, in some way, impact the preparation of master production schedules in the manufacturing sector.